Experimental research of the motions of compressed air foam in horizontal cylindrical channel - Grachulin Александр (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2016)
Described the experimental installation for research of the movement of compressed air foam in the hose line of compressed air foam system. Proposed the technique of these research. Are given preliminary experimental results of change of pressure, gas content, density and velocity along the hose line when moving compression foam. The analysis of the results.